Efektivitas Perubahan Fase Material KCl/H2O sebagai Sistem Pendingin Ikan Laut - Iqbal Alief; Sri Rahayu Alfitri Usna; Astuti Astuti; Sri Oktamuliani (Universitas Andalas, 2024)
This study aims to determine the effectiveness of phase change material (PCM) KCl/H2Oas a fish cooling system. KCl/H2Ois a eutectic PCM of hydrate salts with a melting temperature of -10.7 °Cand an enthalpy of 273 kJ/kg. The samples tested were Kuwe marine fish with a mass of 1 kg (4 heads). The variation in fish mass to KCl/H2Ois 1:0.5, 1:1, 1:2, and 1:3. The process of changing the temperature of the fish cooling system every time is measured using the DS18B20 temperature sensor. Based on the study's results, KCl/H2Ois effective in reducing fish temperature by -0.22 °C/minute.The use of 2 kg KCl/H2O is effective in maintaining fish temperature in the temperature range of0 to 5 °C for 20 hours, and the use of 3 kg KCl/H2Ois good in maintaining fish temperature in the lower temperature range of -5 to 0 °C for 16 hours. In terms of economy, the cost of handling the fish cooling process using KCl/H2Ois six times greater than conventional cooling, so this system is less recommended.